Application Of Edible Coating Chitosan and Nanochitosan Shrimp Shells on Heat-Polymerized Acrylic Resin Based on Water Absorption - Ria Koesoemawati; Kadek Dwi Dessy Sapitri; Kadek Ayu Wirayuni (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: The base material commonly used for removable dentures is heat-polymerized acrylic resin. Its weakness is water absorption, causing dimensional changes, discoloration, and effects on mechanical properties such as transverse strength, hardness, and biocompatibility. Shrimp shell chitosan, a natural biopolymer, can form a thin film coating and has the potential to be used as an edible coating. The purpose of this study was to examine the effect of applying edible chitosan and nanochitosan coatings from shrimp shells to heat-cured acrylic resin in inhibiting water absorption. Materials and Methods: The research design was a true experimental laboratory with a posttest-only control group design. Thirty plates measuring 60X10X2.5 mm were divided into 5 groups, namely 1 control group without coating (distilled water) and 4 treatment groups with 2% chitosan, 3% chitosan, 2% nanochitosan, and 3% nanochitosan Aldrich® shrimp shells. The coating was applied by immersion for 5 minutes and dried for 1 hour for all treatment groups. Water absorption was tested by immersion in distilled water for 7 days at a temperature of 37±2 °C, calculated according to the formula in ISO 4049. Results and Discussion: One-way ANOVA analysis showed significant differences (p<0,001). The LSD post-hoc test showed that all treatment groups differed significantly from the control group (p=0.001). Meanwhile, there were no significant differences between the chitosan and nanochitosan treatment groups (p>0.05). Conclusion: It can be concluded that the application of 2% and 3% edible chitosan and nanochitosan coatings from shrimp shells can inhibit water absorption in a heat-polymerized acrylic resin base.